Asymmetric Information, Portfolio Managers, and Home Bias - Dziuda, Wioletta; Mondria, Jordi (Review of Financial Studies, 2012)
We propose a model of delegated asset management that can explain the following empirical regularities in international markets: the presence of home bias, the lower proportion of mutual funds investing domestically, and the higher market value of mutual funds investing domestically. In the model, fund managers choose whether to specialize in domestic or foreign assets. Individual investors are uncertain about managers' abilities, and they are more informed about domestic markets. This makes domestic investments less risky and generates home bias. Home bias is magnified because higher-ability managers specialize in domestic assets, making them even more attractive to the investors.